Statistical analysis and inter-comparison of erythemal solar radiation for Athalassa and Larnaca, Cyprus. (October 2017) - Kalogirou, S.A.; Pashiardis, S.; Pashiardi, A.
Abstract: A statistical analysis and inter-comparison of the erythemal ultraviolet radiation (UVER) at two sites in Cyprus representing two different climate regimes of the island (Athalassa-inland plain vs Larnaca-coastal location) covering the period January 2013–December 2015 is presented. Mean annual and mean monthly daily totals of the UVER irradiation and their frequency distribution at both sites are computed and discussed. UVER irradiance fluctuates between 0.054 W m −2 in December to 0.227 W m −2 in July at solar noon at Athalassa. The values at Larnaca are lower than in Athalassa and they fluctuate between 0.043 W m −2 in December and 0.172 W m −2 in July at solar noon. The total accumulated UVER irradiation along a mean year reaches 1142 kJ m −2 at Athalassa and 909 kJ m −2 at Larnaca. Large fluctuations of the daily UVER irradiation are observed in the spring months and November, which are mainly due to unstable meteorological conditions during the transition from cold to warm weather and vice versa. During summer the daily UVER radiation exceeds the value of 6 kJ m −2 at Athalassa and 4.8 kJ m −2 at Larnaca, while during the winter season the lowest is about 0.2 kJ m −2 at both sites. Statistical relationships between UVER and other radiation components (UVA, global radiation, clearness index and relative optical air mass) are established. The UV Index reaches high (6–7) or very high (8–10) values in 58.1% of the cases in Athalassa, whereas in Larnaca these values are reached in 38.8%. It is observed that the cumulative doses of UVER during an average year range from 9087 Standard Erythemal Dose (SEDs) in Larnaca to 11418 SEDs in Athalassa. The most common skin type in Cyprus, phototype III (about 70% of the population), could receive an annual cumulative dose between 2596 Minimum Erythemal Doses (MEDs) in Larnaca to 3262 MEDs in Athalassa. Highlights: Statistical analysis of ultraviolet erythemal radiation. Monthly and diurnal variation of ultraviolet erythemal radiation. Statistical relationships between ultraviolet erythemal and other radiation components. Calculation of UV Index. Estimation of the cumulative doses during an average year for the four skin phototypes.